THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK DISCIPLINE ON THE WORK ACHIEVEMENT OF TEACHERS OF SMAN 18 KABUPATEN TANGERANG - Jubaedah Jubaedah; Peni Sawitri (Dinasti International Journal of Education Management And Social Science, 2022)
This study aims to determine whether there is an influence of Transformational Leadership and Work Discipline on Teacher Work Achievement at SMAN 18 Tangerang regency. Data were collected based on a questionnaire for 45 respondents from SMA N 18 Tangerang regency. The research method used is descriptive method. This method is used to provide a systematic, actual and accurate description of the facts and the influence of the phenomena studied. To answer the research problem, the data analysis technique used is multiple partial regression analysis. The results showed that the variables of transformational leadership and work discipline together (simultaneously) had a significant effect on teacher work performance at SMA Negeri 18 Tangerang Regency by 77.8% while the remaining 22.2% were other factors not discussed in this study. The regression coefficient for transformational leadership (b1) is 0.575 and the regression coefficient for work discipline (b2) is 0.312, meaning that each addition of one unit of transformational leadership and work discipline will increase teacher work performance by 0.575 and 0.312 units. The better the application of work discipline, the better the performance of teachers at SMA Negeri 18 Tangerang Regency.